Phytoplankton composition of El Abrevadero reservoir, Jantetelco, Morelos, Mexico - Carrasco Vargas, Ulises Yair; Díaz Vargas, Migdalia; Molina Astudillo, Francisca Isela; García Rodríguez, Judith; Elizalde Arriaga, Edgar Eduardo (Acta Universitaria, 2015)
This work analyzes the phytoplankton composition of El Abrevadero reservoir in the town of Tenango (18º 42’ N and 98º 46 W), Jantetelco, Morelos. Monthly sampling during the period May 2008 to May 2009 in three collection sites (two littoral zone and one limnetic zone) was made. A total of 28 415 org/ml was recorded, and the highest abundance was detected during the dry season; station three (mention which zone is this instead of the station number) showed the highest values. Four taxonomic classes: Euglenophyceae (10 329 org/ml) with two genera, Chlorophyceae (8953 org/ml) with 16 genera, Cyanophyceae (6818 org/ml) with six genera and Bacillariophyceae (2315 org/mL) with eight genera were recognized.